Analisis Konsentrasi Pasar di Industri Maskapai Penerbangan Komersial Domestik Indonesia (2019-2024): Bukti Tingkat Perusahaan vs Tingkat Grup - Chandaka, Fernando Dhiraputra; Ariani, Mintarti (RUBINSTEIN, 2026)
This study examines competition in Indonesia’s domestic commercial airline industry during the 2019–2024 period. While prior studies have measured market concentration at the firm level, few have examined how ownership-group structures may reshape our understanding of effective competition. Using a quantitative descriptive approach, the study addresses this gap by applying the Four-Firm Concentration Ratio (CR4) and the Herfindahl-Hirschman Index (HHI) at two distinct levels of analysis: firm level and group level. The findings reveal a tight oligopoly, with CR4 consistently remaining above 70% and HHI values declining to the moderately concentrated category in 2023–2024. However, group-level HHI remained highly concentrated, exceeding 3,900. Parallel conduct, such as synchronized baggage policy changes, market segmentation, similar service offerings, and firm consolidation, was observed alongside the effects of the market structure. This condition suggests limited competition, which may influence pricing strategies and consumer welfare. These findings emphasize that firm-level analysis may underestimate the true degree of market concentration when group affiliations are ignored. Practically, group-level dominance provides a foundation for monitoring market concentration at the group level rather than solely at the individual-firm level. Effective competition in the industry remains highly concentrated within two dominant groups.